QUALITY OF LIFE AND SATISFACTION OF PARALYMPIC SPORT PRACTICERS AND NON-PRACTICES IN RELATION TO THEIR ASSISTANT TECHNOLOGIES - Lima Magalhães, Beatriz; Melo Yasuda, Thiara; Rocha Pereira, Edmara Campos; Lopes Bispo, Sarah; Santana Parreira, Samara Lamounier (International Journal of Movement Science and Rehabilitation, 2019)
To compare the perception of the level of quality of life and the satisfaction of users of assistive technologies, of people with sequelae of neurological injuries and amputations athletes and not practicing sports activity; a descriptive, cross-sectional and quantitative research was carried out. To evaluate the quality of life QV-WHOQOL-BREF was applied for satisfaction with regard to assistive technologies, the QUEST 2.0 questionnaire. The perception of QoL of athletes is better than that of non-practitioners. The domains that most influenced these results were: physical, psychological and social relationship. As for the satisfaction with the TAs, both groups are more or less satisfied.